PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS TERPADU - Angga, Angga; Suryani, Nunuk; Djono, Djono (Candi, 2018)
The purpose of this research is to improve creativity and learning outcomes history students class VIII A SMP Negeri 3 Kebakkramat Karanganyar Regency academic Year 2016/2017 by applying the model koopertaif type Talking Stick and the audio-visual media.This research is classroom action research (CAR). Research conducted in two cycles, with each cycle consisting of planning, implementation, observation and reflection. The research subject is the students, teachers and the teaching and learning process in class VIII A SMP Negeri 3 Kebakkramat. Data sources come from students, teachers and the teaching and learning process. Data collection technique is conducted by using testing, observing, interviewing, document analizing. The validity techniques of the data is using triangulation techniques and data sources triangulation method. Data analysis using comparative descriptive technique and qualitative data analysis. Research procedures are spiral model (Planning, Acting, Observing and Reflecting). The results showed that:(1) Application of model Cooperative learning type Talking Stick with the audio-visual media can enhance the creativity of student learning on the learning of Social Sciences in students of grade VIII A SMP Negeri 3 Kebakkramat. The results of the creativity study on thepre-cycle of 50,30%, then in cycle I the results of the creativity study of 71,92 %, whereas in cycle II the results of the creativity study of 81,15 %. (2) Application of model Cooperative learning type Talking Stick with the audio-visual media can improve student learning outcomes in the learning of Social Sciences in students of grade VIII A SMP Negeri 3 Kebakkramat. Learning outcomes on thepre-cycle of 53,12%, then in cycle I the results of the study by 75%, whereas in cycle II the learning outcomes of 84.37%.